DAMPAK PENGGUNAAN SMARTPHONE DALAM PEMBELAJARAN BAHASA INGGRIS (PERSEPSI MAHASISWA) - BARAKATI, DIJEY PRATIWI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This research entitled â€œDampak Penggunaan Smartphone dalam Pembelajaran Bahasa Inggris (Persepsi Mahasiswa)â€. The objectives of this research are to identify and analyze the impacts of using smartphone in learning English based on Bakerâ€™sÂ (2005) theory. The impacts are portability, colaboration and motivation. The researcher uses qualitative approach in order to find out studentsâ€™ perception about the impacts of using smartphone in learning English. The social situation in this research isÂ Â the 4th semester students at the Faculty of Letters. The researcher took 25 students who use smartphone as samples of this research.Â The instruments of this researh are questionnaires and open-ended question. The results of this research show that there are some impacts of using smartphone in learning English according to studentsâ€™ perception. They are portability, collaboration,Â motivation and according to studentsâ€™ perception smartphone can increase their ability in learning English. These results support Barker et al., theory about the impact of using mobile phone in learning English. But there are negative impacts from portability, the students as stated smartphone can be a tool for cheating, and it tends to make students to do things instantly and can be addicted to it. Keyword: Impact, Perception, Smartphone, Learning English.